Hydrodynamics of a three-phase external-loop airlift bioreactor - Freitas, Carla Maria Duarte de (1999)
The effect the distributing plate orifice diameter, airflow rate, solids loading and solids density on the hydrodynamic characteristics – gas holdup, circulation time and liquid velocity – of a threephase external-loop airlift reactor was characterized. It was observed that the gas distributor has a small effect on riser gas holdup, circulation time and downcomer liquid velocity. On the contrary, the airflow rate, solids loading and solids density significantly affect the hydrodynamic characteristics of the external-loop airlift reactor.